A call to integrate economic, social and environmental motives into guidance for business support for the transition to a circular economy - Anne P. M. Velenturf; Paul D. Jensen; Phil Purnell; Juliet Jopson; Norman Ebner (Administrative Sciences, 2019)
A broad range of organizations, from small and medium-sized enterprises to large multi-nationals, are interested in adopting circular economy practices. A circular economy can help companies make better use of materials by minimizing the input of natural resources, reducing waste, and optimizing the economic, social, technical and environmental costs and benefits of materials and products throughout their lifecycle. Despite the interest of companies in a circular economy, only 9% of material flows in the global economy are circular. There is formal guidance for those offering business support with the aim to expedite the transition to a circular economy. However, support measures narrowly confine the role of companies and the motivations of business managers to the economic realms, assuming that companies are solely driven by monetary factors. Conversely, pluralist economic views emphasize the broader role of companies in society: for example, in respect of the well-being of their staff and the communities in which they reside. Indeed, our practical experiences of business support have brought alternative motivations to explore a circular economy to the fore. We argue that business support should stem from a broader conception of the role of business in society. The diverse motivations and willingness of business managers to engage in a circular economy should be investigated further with results feeding into broader and more inclusive business support guidelines in the future to accelerate the transition towards a circular economy.
Keywords: 350; circular economy; circular business model innovation; industrial ecology; waste and resource management; sustainable production and consumption; human well-being; corporate social responsibility; regional development; stakeholder engagement; business management